Computer-based Malay articulation training for Malay plosives at isolated, syllable and word level - Ting, Hua Nong; Yunus, Jasmy; Vandort, S.; Wong, L. C. (2003)
This paper describes the use of computer as an articulation training system for Malay plosives at isolated, syllable and word level. The proposed system is more convenient than the traditional speech analyzing tools such as Electropalatograph, where the latter requires an external electronic circuit to be attached into the mouth of client. The system is designed in a way that is user friendly and easy to use for the speech-language pathologist or even the client. The client undergoes speech training by just taking into the microphone and the system is able to recognize the sounds and classify them accordingly. Audio and visual feedback is used to help the.client to identify his or her articulation errors as well as to make comparisons between hisher articulation models with the standard model. The system can be used for both children and adults.